2017
DOI: 10.1016/j.jpor.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of dental implant diameter and length according to bone quality determined by finite element analysis and optimized calculation

Abstract: According to the variables determined using Latin hypercube sampling, 500 FE models were constructed and analyzed under each of the loads following the construction of response surfaces with the MES as a response value. D and L were minimized by optimized calculation with the MES limited to the physiological limit with reference to the mechanostat theory.Results: The MES was significantly influenced by D more than L, and could be restricted to the physiological limit unless both C and T were small. Finite Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…The diameter and the length, which are the most studied variables, both strongly impact the mechanical environment of the peri-implant bone. It has been shown that a larger length reduces stress in the bone but not as much as a larger diameter [7]. The placement of the implant in the bone is also frequently studied, and some papers have considered its insertion depth [8] or inclination in the bone [9].…”
Section: Introductionmentioning
confidence: 99%
“…The diameter and the length, which are the most studied variables, both strongly impact the mechanical environment of the peri-implant bone. It has been shown that a larger length reduces stress in the bone but not as much as a larger diameter [7]. The placement of the implant in the bone is also frequently studied, and some papers have considered its insertion depth [8] or inclination in the bone [9].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to increase the bone-to-implant contact area have focused on increasing the diameter and/or length of implants, or altering the fixture micro and/or macro design. 6 Some researchers believe that the implant diameter is a more important factor in decreasing stress in bone, 7 while according to others, the implant length has a more significant effect on the strain/stress distribution in bone around dental implants. 8 On the other hand, it has been shown that neither the implant diameter nor its length are as important as the technique of surgery, sufficient primary stability, and pre-and postoperative oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…9 Larger implants, in terms of both diameter and length, improve the stress/strain distribution patterns; however, in many clinical situations, the alveolar bone does not have sufficient thickness or height for the insertion of such implants. 6 There are cases in which the clinician must choose between inserting a longer implant with a smaller diameter or decreasing the bone height and using a shorter implant with a greater diameter. The subsequent crestal bone resorption is another concern in changing the stress/strain distribution pattern, as the crown-implant ratio changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures occur when the skeleton is subjected to external forces greater than the maximum load. Generally, the larger the maximum load, the better is the bone quality . Deflection is the degree of resistance to distortion.…”
Section: Results and Analysismentioning
confidence: 99%